Production, characterization and stabiliity of liposomes containing creatine - Pereira, Rafael; Krawczak, Katianne Wolf; Muller, Edson Ireneu; Pinto, Afonso Gabriel Inquelmann; Duarte, Marta Maria Medeiros Frescura; Rhoden, Cristiano Rodrigo Bohn; Krause, Luciana Maria Fontanari; Mortari, Sergio Roberto (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
Creatine is a compound of three amino acids that is widely used as an ergogenic resource in sports, because it has the ability to form Creatine Phosphate (PCr) in the mitochondria and increase ATP resynthesis. Liposomes are nanoscale lipid vesicles used to increase the stability, viability and bioavailability of molecules such as drugs. In this work, creatine-containing liposomes were obtained by the ethanol injection method, producing liposomes with an average diameter of 124.5 nm, a polydispersity index of 0.141, and a zeta potential of -3.9 mV. Stability studies showed that the creatine-containing liposomes are stable for up to 90 days when stored at room temperature (± 25 ºC).